The benefits and limitations of reaction cell and sector field inductively coupled plasma mass spectrometry in the detection and quantification of phosphopeptides. (15th January 2015) - Maes, Evelyne; Brusten, Wilfried; Beutels, Filip; Baggerman, Geert; Mertens, Inge; Valkenborg, Dirk; Landuyt, Bart; Schoofs, Liliane; Tirez, Kristof
<x xml:space="preserve">Abstract</x> RATIONALE The phosphorylation of proteins is one of the most important post‐translational modifications in nature. Knowledge of the quantity or degree of protein phosphorylation in biological samples is extremely important. A combination of liquid chromatography (LC) and inductively coupled plasma mass spectrometry (ICP‐MS) allows the absolute and relative quantification of the phosphorus signal. METHODS A comparison between dynamic reaction cell quadrupole ICP‐MS (DRC‐Q‐ICP‐MS) and high‐resolution sector field ICP‐MS (SF‐ICP‐MS) in detecting signals of phosphorus‐containing species using identical capillary LC (reversed‐phase technology) and nebulizer settings was performed. RESULTS A method to diminish the reversed‐phase gradient‐related signal instability in phosphorus detection with LC/ICP‐MS applications was developed. Bis(4‐nitrophenyl)phosphate (BNPP) was used as a standard to compare signal‐to‐noise ratios and limits of detection (LODs) between the two instrumental setups. The LOD reaches a value of 0.8 µg L−1 when applying the DRC technology in Q‐ICP‐MS and an LOD of 0.09 µg L−1 was found with the SF‐ICP‐MS setup. This BNPP standard was further used to compare the absolute quantification possibilities of phosphopeptides in these two setups. CONCLUSIONS This one‐to‐one comparison of two interference‐reducing ICP‐MS instruments demonstrates that absolute quantification of individual LC‐separated phosphopeptides is possible. However, based on the LOD values, SF‐ICP‐MS has a higher sensitivity in detecting phosphorus signals and thus is preferred in phosphopeptide analysis. Copyright © 2014 John Wiley & Sons, Ltd.